Surface Composition and Morphology of Layered Double Hydroxidebased Composite Conversion Coating on Aluminum Alloy - an XRD and SEM Study - Chan, Woei Long; Hussein, Mohd Zobir; Zainal, Zulkarnain; Yahaya, Asmah (Penerbit Universiti Sains Malaysia, 2004)
For particular functions, the natural surface oxide film of aluminum (Al) alloys is treated to form a functional conversion coating (CC). The functional CCs increase the adhesion of the subsequent organic layers such as paint and adhesive (Thompson, 1994). For example, in the widely employed chromate conversion coating (CCC), the “blade-like” surface morphology acts to interlocks the secondary coating, thus enhancing the adhesion (Leggat et al., 2002a&b).